Logistics and Planning of Output Volume - V. I. Pokhabov; V. E. Klichevskaya (Наука и техника)
On the basis of logistics conception the paper considers an adaptation of an enterprise to environmental changes with due account of its emergement properties. Taking into account emergement properties of an enterprise a logistics method for planning an optimum movement of the material flow is proposed in the paper.